Circular forms of Uukuniemi virion RNA: an electron microscopic study. - Hewlett, M J (1977)
Because the ribonucleoprotein forms of the segments of the Uukuniemi virus genome have previously been characterized as circular, we examined the isolated RNAs by electron microscopy under conditions of increasing denaturation. After spreading under moderately denaturing conditions (50 or 60% formamide), 50 to 70% of the molecules were circular. Increasing the formamide concentration to 70 and 85% decreased the number of circular forms, and only linear forms were observed after incubation of the RNA at 60 degrees C for 15 min in 99% formamide. When spread from 4 M urea-80% formamide--another condition known to denature RNA--only 5 to 30% circular molecules were observed. Pretreatment of the RNA with 0.5 M glyoxal at 37 degrees C for 15 min prior to spreading from 50% formamide gave less than 5% cirucular forms. Length measurement of the molecules showed that they were not significantly degraded by any of the methods employed. The circular molecules were destroyed by treatment with pancreatic RNase, but were unaffected by DNase or proteinase K treatment. After complete denaturation of the RNA, the circles could be reformed under reannealing conditions. We conclude that the three size classes of RNA that comprise the Uukuniemi virus genome are circular molecules probably maintained in that form by base pairing between inverted complementary sequences at the 3' and 5' ends of linear molecules.